Farmers' Perception and Participation in Bat Conservation in Agricultural Areas of Banyuwangi, East Java, Indonesia - Adelia, Venika Shafa; Priyambodo, Swastiko; Hindayana, Dadan; Wiantoro, Sigit (Universitas Gadjah Mada, 2025)
Pests in the agricultural sector cause huge losses to farmers' production and income. Sustainable pest management, such as the utilization of natural predators, is important to maintain agricultural productivity. In Banyuwangi, East Java, Indonesia fruit-eating bats pose a threat to horticultural yields, although their ecological roles as pollinators and seed dispersers are recognized. Conflicts between bat conservation efforts and farmers' needs arise because most farmers view bats as pests. This study examines farmers' perceptions of bats and their participation in bat conservation in Banyuwangi, as well as the factors that influence their attitudes. Based on interviews and data analysis in three sub-districts, this study found that farmers' knowledge on the benefits of bats is not always directly proportional to their positive attitude towards them. To resolve this conflict, a management strategy that includes education, incentives and collaboration with farmers is suggested. Through this approach, a balance between bat conservation and agriculture sustainability is expected to be realized, providing long-term benefits for the ecosystem and agricultural productivity in the region.